AREAS OF USE OF HIGH-STRENGTH CAST IRON - Tojiboyev Muhammadjon Muhitdin og'li ("Conference on Universal Science Research 2023", 2023)
Cast iron is one of the oldest ferrous metals used commercially. It consists mainly of iron (Fe), carbon (C), and silicon (Si), but may also contain traces of sulfur (S), manganese (Mn), and phosphorus (P). It has a relatively high carbon content of 2% to 5%. It is usually brittle and inflexible (that is, it cannot be bent, stretched, or hammered into shape) and has relatively weak tensile strength. Cast iron members tend to break with small deformations. However, cast iron has excellent compressive strength and is usually used for structures that require this property. Cast iron's composition, production method, properties, and applied heat treatment are important in determining its finality.